Factors Affecting The Outcome of The Insurance Activity an Applied Study on Takaful Insurance Companies Operating in Syria (Journal of Hama University, 2020)
This study aimed to identify the most important factors affecting the outcome of the insurance activity (surplus / deficit), as the multivariate regression method was used to determine the factors affecting the outcome of the insurance activity of the Syrian Takaful insurance companies, through the quarterly data of the Takaful insurance companies operating in Syria during the period from 2008 to 2017, the outcome of the insurance activity was relied upon as a dependent variable, and on a set of independent variables (net written premiums, net claims, reinsurance commissions, other incomes, net investment income, administrative and general expenses), neighborhood The study sample included the Takaful insurance companies in Syria    The research reached a set of results with a variation in the values ​​of the output of the insurance activity for the studied insurance companies. There is a negative impact of statistically significant for both investment income and reinsurance commissions This could be explained by the weak investment policy of these companies, in addition to the presence of a positive impact of other revenues, while this study concluded that there was no statistically significant effect for both net claims, net earned premiums, general and administrative expenses.